SEMIOTIC STUDY OF THE MEANING OF THE ORAL LITERARY TEXT OF THE COFFEE MANTRA IN THE LAND OF GAYO - Yusdithira Rifqhy Hikmawan Siregar; Mauly Purba; Ikhwanuddin Nasution (Journal of Social Research, 2023)
Coffee dominates into the sphere of association and social life. The presence of coffee shops in recent years is also one of the factors of the phenomenon of drinking coffee, such as the form of campaigns that affect the mindset of social communities. The research method used to research Coffee Mantras in Gayo land is the Qualitative descriptive method. This research involves various types of disciplines, both from humanitarian, social, or natural sciences. There are several theories about the origin of the Gayo Tribe. Local people believe that the name Gayo comes from the word pegayon which means a source of clear water where sacred fish and crabs are located. One version says the origin of the Gayo Tribe is related to the Linge Kingdom which was founded around 416 Hijri or 1025 AD. As a result of the excavation of these ancient sites, prehistoric human skeletons were found. After scientific research, the human skeleton found, ranging in age from 3,580 to 4,400 years. Mantra Kopi in the point of view of the Gayo people, is a form of oral literature that will never be abandoned. They believe that with coffee that is spelled or chanted will bring good things